Two new species of freshwater sponges from Neotropical and Afrotropical Regions - Pinheiro, Ulisses; Calheira, Ludimila; Martins, Celina; Janson, Liesl; Taylor, Ricky; Samaai, Toufiek (Zootaxa, 2020)
Geographic distributions of freshwater sponges are related to the geological and climatic history of the continents, on the presence of gemmules and the morphological complexity of this resistant body to withstand change. Gemmules are characteristic of the freshwater Families Spongillidae, Metaniidae and Potamolepidae. However, Acanthotylotra alvarengai, Echinospongilla brichardi and a number of other species within the genus Potamolepis do not produce gemmules. Potamolepis is endemic to the Afrotropical region with seven valid species. African freshwater sponges however, are mostly known from a single specimen (the holotype), due to the scarcity of material from these freshwater systems. In the present study, we describe two new species of non-gemmule bearing freshwater sponges from the Neotropical and Afrotropical Regions.